Anisotropic grain growth in iron-carbon films at high electric current densities. (15th March 2020) - Brede, Thomas; Kirchheim, Reiner; Volkert, Cynthia A.
Abstract: We investigate the effect of direct electric current (DC) on grain growth in 100 nm thick iron-carbon films with carbon concentrations between 0.7 to 4.4 at%. The application of DC-current during annealing at 550 °C confirms the expected transport of carbon in the direction of the electric current and the unexpected formation of elongated, abnormally large carbide and ferrite grains along the current direction in the carbon-rich regions. The formation of elongated grains is explained by electromigration-induced carbon flux divergences that result from the carbide precipitates. This presents a possible scenario for controlling microstructure evolution in iron by using DC electric currents. Changes for alternating current (AC) pulses had been observed before. Graphical abstract: Image, graphical abstract